Accelerated Self-Photopolymerization of Phenolics in Microdroplets Contributes to the Brown Carbon Formation - Haoran Yu; Xinrui Yang; Longgang Chu; Ruobing Wang; Zhaoyue Sun; Juan Gao; Davide Vione; Bing Wu; Hongqiang Ren; Chongqin Zhu; Joseph S. Francisco; Cheng Gu (Journal of the American Chemical Society, 2026)
Abstract While phenolic compounds are recognized as key atmospheric precursors of brown carbon (BrC), the mechanisms governing their interfacial transformation into BrC aerosols, particularly at the microdroplet air–water interface (AWI), remain incompletely characterized. This study investigated the photolysis of phenolic compounds in microdroplets under UV irradiation, revealing a transformation efficiency 2 orders of magnitude higher than that in bulk solutions. Through integrated Fourier transform ion cyclotron resonance mass spectrometry, liquid chromatography–mass spectrometry, and fluorescence excitation–emission matrix spectrum, we identified interfacial-confined oligomerization as the dominant pathway generating BrC with oligomer characteristics. Multiscale theoretical simulations unveiled that the AWI functions as a key mediator through a synergistic mechanism: it not only drives the spontaneous accumulation of phenols at the interface, but also enhances their photon absorption efficiency via asymmetric interfacial H-π hydrogen bonding, as evidenced by a critical 24.7% increase in the molar extinction coefficient at 298 nm. Together, these dual effects synergistically facilitate photon capture and subsequent phenoxy radical generation. Our results establish the AWI as photochemical nanoreactors that fundamentally alter atmospheric BrC formation kinetics, providing a mechanistic framework to reconcile field observations of rapid aerosol aging under humid conditions, while challenging current model assumptions about phenolic transformation time scales.